If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -3 = -3x + -3 Reorder the terms: -3 + 3x = -3x + -3 Reorder the terms: -3 + 3x = -3 + -3x Add '3' to each side of the equation. -3 + 3 + 3x = -3 + 3 + -3x Combine like terms: -3 + 3 = 0 0 + 3x = -3 + 3 + -3x 3x = -3 + 3 + -3x Combine like terms: -3 + 3 = 0 3x = 0 + -3x 3x = -3x Solving 3x = -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 3x + 3x = -3x + 3x Combine like terms: 3x + 3x = 6x 6x = -3x + 3x Combine like terms: -3x + 3x = 0 6x = 0 Divide each side by '6'. x = 0 Simplifying x = 0
| 4x^2+16x=48 | | 5x^2=3+3x | | x+15=55 | | n+8=3n-6 | | x+8=3n-6 | | 4x+2=6x-10 | | 25-X=12 | | 3(5z-1)-5(z+8)=2(z+1) | | 12k-3(5+5)=52 | | 2x+x=150 | | 2xm=18 | | 6(3z-1)-3(z+5)=10(z+1) | | 1.17x=140 | | 72y+-54+9y= | | 7t-3t+4t=-25 | | -36-3y+18=-21y+72+12y | | 0.01=2x-0.19 | | -98=-14x | | -2k=9 | | 6=x+9 | | 47=x-71 | | -4.9t^2+50t=0 | | -2+4.3=10.7 | | z+13=-3 | | 2(2x+3y)=0 | | 1.4(x+3.5y)+2(3.5x+1.7y)= | | (6x+2)2=4x+36 | | 5x+x=42 | | 5x+y=42 | | 80=2x^2+14x | | 80=2x^2 | | 4x+20=3x |